2013
DOI: 10.1093/ageing/aft171
|View full text |Cite
|
Sign up to set email alerts
|

Preparation to care for confused older patients in general hospitals: a study of UK health professionals

Abstract: Background and Objective: in the UK, two-thirds of patients in general hospitals are older than 70, of whom half have dementia or delirium or both. Our objective was to explore doctors, nurses and allied health professionals' perceptions of their preparation to care for confused older patients on general hospital wards.Methods: using a quota sampling strategy across 11 medical, geriatric and orthopaedic wards in a British teaching hospital, we conducted 60 semi-structured interviews with doctors, nurses and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 15 publications
3
96
0
1
Order By: Relevance
“…Items reflected behavioral challenges and use of nonpharmacological strategies (e.g., "If a person with [AD] feels threatened by you, he/she will be more cooperative"; and "It doesn't matter if you introduce yourself to a person with [AD] because they can't remember your name") (Griffiths, Knight, Harwood, & Gladman, 2014;Teri et al, 2009). The final scale included 27 true/fals e items.…”
Section: Measurementioning
confidence: 99%
“…Items reflected behavioral challenges and use of nonpharmacological strategies (e.g., "If a person with [AD] feels threatened by you, he/she will be more cooperative"; and "It doesn't matter if you introduce yourself to a person with [AD] because they can't remember your name") (Griffiths, Knight, Harwood, & Gladman, 2014;Teri et al, 2009). The final scale included 27 true/fals e items.…”
Section: Measurementioning
confidence: 99%
“…The National Audit of Dementia Care in General Hospitals (2011) found that two thirds of staff (across all job roles) felt they had insufficient skills in caring for people with dementia (Young et al, 2011) and this finding has been replicated in other studies of hospital staff (Griffiths et al, 2014).…”
mentioning
confidence: 95%
“…There is a lack of prequalification dementia training for both nurses (Pulsford, Hope, and Thompson, 2006) and doctors (Hasselbalch et al, 2007;Tullo & Allan, 2011). In addition, post-qualification training can be variable, depending on factors such as the employer (Doherty and Collier 2009;Royal College of Psychiatrists, 2013) or the ability of managers to release staff from an already busy and pressurised ward environment (Griffiths, Knight, Harwood, & Gladman, 2014). This results in varying levels of knowledge and skills amongst general hospital staff.…”
Section: Introductionmentioning
confidence: 99%